Low high-temperature hardness: a drawback of current ODS copper alloy Cu-Al2O3 applied in monoblock-type components fabricated by HIP - Wu-Qingliang Peng; Yu-Ping Xu; Fang-Yong Du; Yu Tian; Zhen Chen; Qiang Li; Guang-Nan Luo; Hai-Shan Zhou (Nuclear Fusion)
Copper-based alloys, including precipitation hardened copper alloys and oxide dispersion strengthened (ODS) copper alloys, are considered highly promising heat sink materials for fusion divertor due to their excellent thermal conductivity and high strength. In this work, components consisting of five tungsten monoblocks and utilizing ODS copper alloy Cu-Al _2 O _3 (GlidCop Al-15) were successfully manufactured via the hot isostatic pressing (HIP) technique. Plastic deformation with an average twisting degree of 22° and circular indentations with an average depth of 88.33 μ m were observed at the toroidal gap of the W/Cu/GlidCop Al-15 mock-up, compared to a twisting degree of 0° and a depth of 35.55 μ m in a similarly manufactured W/Cu/CuCrZr mock-up. High heat flux (HHF) thermal fatigue tests at 15 MW m ^−2 were conducted to evaluate the durability of the components. Unexpectedly, premature leakage failure occurs at the same toroidal gap. The relatively lower hardness of GlidCop Al-15 (14.90 ± 1.76 HV at 680 °C) at high temperatures compared with CuCrZr (45.34 ± 1.77 HV at 680 °C) has been identified as the primary factor leading to easy circular indentation at the toroidal gap during the HIP fabrication process, thereby increasing the likelihood of crack initiation under cyclic HHF loading conditions. This paper presents a new perspective on the application and performance enhancement of ODS copper alloy Cu-Al _2 O _3 in the manufacturing of divertor components.